Lactobacillus acidophilus Membrane Vesicles as a Vehicle of Bacteriocin Delivery - Dean, Scott N.; Rimmer, Mary Ashley; Turner, Kendrick B.; Phillips, Daniel A.; Caruana, Julie C.; Hervey, William Judson; Leary, Dagmar H.; Walper, Scott A. (Frontiers in Microbiology, 2020)
Recent reports have shown that Gram-positive bacteria actively secrete spherical nanometer-sized proteoliposome membrane vesicles (MVs) into their surroundings. Though MVs are implicated in a broad range of biological functions, few studies have been conducted to examine their potential as delivery vehicles of antimicrobials. Here, we investigate the natural ability of Lactobacillus acidophilus MVs to carry and deliver bacteriocin peptides to the opportunistic pathogen, Lactobacillus delbrueckii. We demonstrate that upon treatment with lactacin B-inducing peptide, the proteome of the secreted MVs is enriched in putative bacteriocins encoded by the lab operon. Further, we show that purified MVs inhibit growth and compromise membrane integrity in L. delbrueckii, which is confirmed by confocal microscopy imaging and spectrophotometry. These results show that L. acidophilus MVs serve as conduits for antimicrobials to competing cells in the environment, suggesting a potential role for MVs in complex communities such as the gut microbiome. With the potential for controlling their payload through microbial engineering, MVs produced by L. acidophilus may be an interesting platform for effecting change in complex microbial communities or aiding in the development of new biomedical therapeutics.